2017
DOI: 10.1080/1478422x.2017.1356981
|View full text |Cite
|
Sign up to set email alerts
|

Summary of studies on the anaerobic corrosion of carbon steel in alkaline media in support of the Belgian supercontainer concept

Abstract: In the Belgian supercontainer concept, a carbon steel overpack will surround high-level waste and spent fuel containers and be encased in a cementitious buffer material. A programme of research has been carried out to investigate and measure the rate of anaerobic corrosion of carbon steel in an artificial alkaline porewater that simulates the aqueous phase in the cementitious buffer material and also in solid cement matrices. This paper highlights the main features of the programme and presents some recent res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…This was assumed to represent the full mass of hydrogen generated during the accumulation period (i.e., no hydrogen was dissolved in the electrolyte, or absorbed by the steel specimens, and the purge gas was sufficient to expel all hydrogen from the cell). It was also assumed that the corrosion was uniform, the surface area was unchanging, and that, given sufficient time, the reaction stoichiometry was described in total by 3normalFnormale+4H2OFe3normalO4+4H2 17 . Regarding stainless steel, the contribution of alloying elements and thus the reaction stoichiometry will be updated to match the composition of the actual corrosion products upon dismantling of the test cells.…”
Section: Methodsmentioning
confidence: 99%
“…This was assumed to represent the full mass of hydrogen generated during the accumulation period (i.e., no hydrogen was dissolved in the electrolyte, or absorbed by the steel specimens, and the purge gas was sufficient to expel all hydrogen from the cell). It was also assumed that the corrosion was uniform, the surface area was unchanging, and that, given sufficient time, the reaction stoichiometry was described in total by 3normalFnormale+4H2OFe3normalO4+4H2 17 . Regarding stainless steel, the contribution of alloying elements and thus the reaction stoichiometry will be updated to match the composition of the actual corrosion products upon dismantling of the test cells.…”
Section: Methodsmentioning
confidence: 99%
“…The Fe(OH) 2 is stable at lower temperatures, but it is predicted to convert to the more thermodynamically stable magnetite (Fe 3 O 4 ) by the Schikorr reaction at higher temperature [19]. The anaerobic corrosion of carbon steel was studied in artificial ground waters and in alkaline solutions [18,29]. Analysis of long-term corrosion tests under a range of conditions, including cementitious environments, found Fe 3 O 4 to be the predominant corrosion product [18].…”
Section: Of 17mentioning
confidence: 99%
“…The anaerobic corrosion of carbon steel was studied in artificial ground waters and in alkaline solutions [18,29]. Analysis of long-term corrosion tests under a range of conditions, including cementitious environments, found Fe 3 O 4 to be the predominant corrosion product [18]. Results for the amount of hydrogen generated depend on which iron corrosion product is used.…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the specimens underwent a short period of rapid corrosion, followed by a drop in the rate to a low and stable value of around 100–200 nm/year. Smart et al [ 11 ] observed that the long‐term corrosion rates of carbon steel under such conditions were insensitive to various environmental parameters including temperature and chloride concentration. The surface analysis was completed on carbon steel wires extracted anoxically from high pH test environments and magnetite was found to be the predominant corrosion product; however, evidence of FeOOH was also found on wires once embedded in cementitious material.…”
Section: Introductionmentioning
confidence: 99%